Optimizing Frame Techniques in 2-Dimensional Video Models in a Learning Perspective: Case Study: Movie Clip Entitled "Perjalanan Jenderal Soedirman" - Chaerudin, Mohamad; Hariawan, Akto; Purnawati, Elly (Journal of Multimedia Trend and Technology, 2024)
As competition for talent increases, electronic media are often used to convey information and influence students' points of view. Animated films are an electronic media that can be used to bridge learning to make it more interesting and provide a new environmental feel for students. According to research results conducted by Computer Technology Research (CRT), people only remember 20% of what they see and 30% of what they hear. Yet people remember 50% of what they see and hear and 80% of what they see, hear and do at the same time. This research aims to evaluate students' level of interest and enthusiasm for learning history through animation media. The research method was created using two-dimensional (2D) animation techniques using frame by frame animation techniques. The data obtained is the result of research from interviews, observations, literature studies and questionnaires conducted at SDN 3 Kutasari which is located in Banyumas Regency. The results of the questionnaire testing used a Likert scale and the average formula for the results of the calculation was 87.9%, so it was included in the agree category or worthy of being shown as a 2D animated short film.